Employing the Role of English Language in the Mode of Thought and Action for Guides Professional Function: The Case of Mentawai Tourism - Elfiondri, Elfiondri; Rasli, Amran; Kartika, Diana; Zaitul, Zaitul (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2023)
Globalization in tourism has penetrated remote indigenous villages of Mentawai, in which English language plays an important role in tourism. Tour guides employ the English language role in the mode of thought and action in performing their professional functions in serving foreign tourists. In Mentawai tourism, guides play important role due to that local people can not speak in English. Study on the English role in relation to the guide professional function is importantly examined to formulate the English roles employed by guides in performing their task (function) as guide in indigenous culture-based tourism, Mentawai. Unfortunately, the role of English language in the language modes for the guides professional function is not examined in Mentawai tourism. The study examines the role of English language in relation to guides professional function in Mentawai tourism. The purpose is to formulate the roles of English language in the mode of thought and action employed by guides in performing their jobs as guide. The study applied qualitative and quantitative methods. Findings are that the English language is employed by guides in three roles. in the mode of thought, English language plays as interactive and communicative role, while in the mode of action (social mode), English language plays as social role. In the social role, English language is employed in various forms of phatic utterance (small talk) with various functions. Guides emloy the social role to build and maintain social relationship with foreign tourists. In the mode of thought, English language is employed to interact verbally with tourists, and to convey tourism-related information to tourists. In conclusion, English language play an importand role socially, interactively, and communicatively in the guide professional function.